Coincidence and Common Fixed Point Theorems in Gb-Cone Metric Spaces (European Journal of Pure and Applied Mathematics, 2021)
In this article, some coincidence and common fixed point results were obtained for four mappings satisfying some special contractive conditions and defined on a G_b-cone metric space (with or without the assumption of normality). Our results generalize recent results in the literature. Two illustrative examples are included and some consequences are supplied.
Keywords: coincidence and common fixed point; $G_b$-Cone Metric Spaces